1) (x + 1)² - (y + 2)²
Soluções para a tarefa
Respondido por
0
(x+1)^2-(y+2)^2= x^2 +2*x*1 +1^2 -y^2-2*y*2 -2^2 =x^2+ 2*x +1 -y^2 - 4*y - 4
=x^2 + 2*x -y^2 - 4*y - 3
=x^2 + 2*x -y^2 - 4*y - 3
Respondido por
0
(x + 1)² - (y + 2)²
=![(x^2+2*x*1+1^2)-(y^2+2*Y*2+2^2) =\\
x^2+2x+1-y^2-2y-4=\\
x^2-y^2+2x-2y-3 (x^2+2*x*1+1^2)-(y^2+2*Y*2+2^2) =\\
x^2+2x+1-y^2-2y-4=\\
x^2-y^2+2x-2y-3](https://tex.z-dn.net/?f=%28x%5E2%2B2%2Ax%2A1%2B1%5E2%29-%28y%5E2%2B2%2AY%2A2%2B2%5E2%29+%3D%5C%5C%0Ax%5E2%2B2x%2B1-y%5E2-2y-4%3D%5C%5C%0Ax%5E2-y%5E2%2B2x-2y-3)
=
Perguntas interessantes
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Administração,
1 ano atrás
Geografia,
1 ano atrás
Física,
1 ano atrás